2023
DOI: 10.3390/ijms241210023
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Related Human Wharton’s Jelly-Derived Stem Cells Differentiation into Osteoblasts, Chondrocytes, Adipocytes and Neural-like Cells—Complete Transcriptomic Assays

Abstract: Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) exhibit multilineage differentiation potential, adhere to plastic, and express a specific set of surface markers—CD105, CD73, CD90. Although there are relatively well-established differentiation protocols for WJ-MSCs, the exact molecular mechanisms involved in their in vitro long-term culture and differentiation remain to be elucidated. In this study, the cells were isolated from Wharton’s jelly of umbilical cords obtained from healthy full-term deliveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
1
1
0
Order By: Relevance
“…After the third passage, the WJ-MSCs were subjected to osteogenic, chondrogenic, adipogenic and neurogenic differentiation. The results of the differentiation were confirmed with specific staining and presented in previous articles [19]. Briefly, in adipoinduced WJ-MSCs stained with Oil Red O, the red lipid droplets were observed, which were not present in the control sample.…”
Section: Evaluation Of Wj-mscs Differentiationsupporting
confidence: 83%
See 1 more Smart Citation
“…After the third passage, the WJ-MSCs were subjected to osteogenic, chondrogenic, adipogenic and neurogenic differentiation. The results of the differentiation were confirmed with specific staining and presented in previous articles [19]. Briefly, in adipoinduced WJ-MSCs stained with Oil Red O, the red lipid droplets were observed, which were not present in the control sample.…”
Section: Evaluation Of Wj-mscs Differentiationsupporting
confidence: 83%
“…Several researchers suggested that the in vitro differentiation of MSCs might decrease the sensitivity of these cells to apoptosis after the transplantation [ 24 , 25 ], while the others obtained the opposite outcomes [ 26 ]. Our previous results obtained after performing RNA-seq on differentiated WJ-MSCs with four lineages indicated that differentiation of WJ-MSCs prior to the transplantation would not be more beneficial than the utilization of undifferentiated cells, considering the expression of apoptosis-related genes in these groups [ 19 ]. Conflicting results emphasize the importance of investigation of the molecular processes occurring during the differentiation of MSCs, not only those engaged in the apoptotic process, to decide whether the differentiation conducted prior to the transplantation of cells would be beneficial.…”
Section: Discussionmentioning
confidence: 99%